2016
DOI: 10.1016/j.envsci.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Multi-level stakeholder engagement in flood risk management—A question of roles and power: Lessons from England

Abstract: A b s t r a c tIn the past years, stakeholder engagement has become more important in flood risk management. On the one hand stakeholder engagement is often declared as a better way of management, a more successful way to reach consensus in policy discussions. On the other hand is the implementation of increasing stakeholder engagement far away from being as positive, where stakeholder engagement often ends in diverse difficulties and conflicts between political leaders and stakeholder groups. This paper aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 140 publications
(101 citation statements)
references
References 33 publications
2
98
0
1
Order By: Relevance
“…IBMs encourage the involvement of local communities and individual building owners in data collection and vulnerability reduction (Thaler and Levin-Keitel, 2016;.…”
Section: Cost Effectivementioning
confidence: 99%
“…IBMs encourage the involvement of local communities and individual building owners in data collection and vulnerability reduction (Thaler and Levin-Keitel, 2016;.…”
Section: Cost Effectivementioning
confidence: 99%
“…This has led to an increasing discussion on changes beyond that of vulnerability and natural hazards (Fuchs 2009;Giupponi and Biscaro 2015). This change has driven a transformation in the role of the state in terms of responsibility sharing and increased individual responsibilities for mitigation and adaptation (Adger et al 2013(Adger et al , 2016Thaler and Levin-Keitel 2016). Additionally, the transformation of responsibility has been encouraged with the implementation of the EU Floods Directive in 2007, such as the introduction of Areas of Potentially Significant Flood Risk (APSFR), 1 insurance companies, or international risk-averse investors which request a re-thinking of the current financial distribution within hazard management (EC 2007;BMLFUW 2011BMLFUW , 2014PenningRowsell 2015;Husby et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that this rise is likely to occur as the flooding in England and Wales in 2013/2014 is thought to be linked to human-induced climate change (Schaller et al, 2016). Furthermore, Bridgwater was used as a case study area by Thaler and Levin-Keitel (2016), who identified the area as having a low capacity to engage in flood risk management due to the lack of socioeconomic structures (i.e. cultural capital, income, and interest).…”
Section: The River Parrett Catchmentmentioning
confidence: 99%